Impact of Social Media Influencers on Behavior and Emotional Wellbeing of Adolescents - Khilza Liaquat; Dr. Imran Muslim (Kurdish Studies, 2024)
Background: This research investigates the relationship between perceived organizational support and innovative work behaviour with expatriate well-being as a mediator and cross-cultural psychological capital as a moderator. Based on organizational support theory and conservation of resources theory, this study aims to determine how organizational support facilitates expatriate psychological health and innovativeness in a foreign context. Methodology: To gather data, a structured questionnaire, and a quantitative method were employed and participants were collected from expatriates of various sectors. Findings: The study shows that the level of perceived organizational support is positively associated with expatriate well-being and innovative work behaviour. Additionally, organizational support positively affects expatriate well-being, which further enhances the innovative work behaviour of expatriates meaning that well-being is an important pathway between organizational support and innovative behaviours among the expatriates. Furthermore, cross-cultural psychological capital amplifies the relationship between POS and expatriate well-being, highlighting the role of psychological capital in international assignments. Implications: From a theoretical perspective, the study adds value to the literature by including psychological capital and well-being as moderating variables that help explain the effect of organizational support on innovation among expatriates. In terms of practical implications, it provides recommendations for organizations that aspire to improve innovation within their global employees by elucidating the importance of support structures and psychological processes. Limitations and Future Directions: Some limitations of the study include having a cross-sectional study only, using self-reported data, and not having a diverse sample; future research should include longitudinal studies, diversified samples, and further investigation of mediating and moderating factors. This research contributes to the literature on expatriate management because it highlights how organizational support, well-being, and psychological capital act together to promote innovative work behaviour.